Neuroprotective Effect of the Isolated Fraction from Biophytum sensitivum on Glutamate-Induced Neurotoxicity in HT22 Neuronal Cells - Guntur, Prasanthi; Sowjanya, Gurugubelli; Deepika, Veera Mani; Sarika, Matta; Bandaru, Nagaraju; Gambhire, Makarand Suresh; Rao, Alla Narayana; Bhavani, Nuziveeti Lakshmi Durga (Indian Journal of Pharmaceutical Education and Research)
Background: The present research paper elucidates to isolate specific fractions from Biophytum sensitivum and assess its ability to protect HT22 neuronal cells (immortalized mouse hippocampal neuronal cells) from glutamate induced neurotoxicity. Materials and Methods: Extraction method was employed for isolation of bioactive compounds from Biophytum sensitivum. These isolated fractions were administered to HT22 neuronal cells that had been subjected to glutamate-induced neurotoxicity. The neuroprotective effects isolated fractions were evaluated using a variety of assays and techniques, including cell viability assays, oxidative stress markers and morphological assessments. Results: Biophytum sensitivum extract demonstrated significant neuroprotective effects against glutamate-induced toxicity in HT22 cells. This neuroprotection may be attributed to the antioxidant properties of isolated compounds, as they were found to mitigate oxidative stress markers that are induced by glutamate. Conclusion: The results of this study are explained in this paper are with clear illustrations containing well demonstrated results. The findings suggest that Biophytum sensitivum holds promise as a rich source of neuroprotective agents and affords a reference version for further exploration of the isolated fractions could contribute to the development of therapeutic interventions for neurodegenerative conditions associated with glutamate-induced neurotoxicity.